Upaya Kepala Madrasah dalam Meningkatkan Kualitas Guru di Madrasah Aliyah Muhammadiyah Kota Gorontalo - Arwin H. Jamalu; Muh. Hasbi; Yinarti Hida (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The objectives of this study are (1) to describe how the principal of the school strives to improve the quality of teachers at Madrasah Aliyah Muhammadiyah in Gorontalo City. (2) To describe/characterize whether there are obstacles faced by the school principal in improving teacher quality at Muhammadiyah Senior High School in Gorontalo City. This research is classified as qualitative in nature, employing a descriptive approach. Data collection techniques include interviews, observations, and documentation. Data analysis is conducted in one stage, namely: Data verification or drawing conclusions. The research results show that the principal of Muhammadiyah Senior High School in Gorontalo City always strives to improve the quality of teachers at Muhammadiyah Senior High School in Gorontalo City by involving all teachers in training and education (DIKLAT) both offline and online. In this study, it can be seen that the challenges faced by the principal in improving teacher quality stem from the lack of adequate facilities and infrastructure, which can hinder the learning process and lead to a decline in educational quality. Since qualified teachers are the most critical factor in improving educational quality, it is essential to optimize educational facilities to support the learning process.